Prevalence of antifolate resistance mutations in Plasmodium falciparum isolates in Afghanistan - Awab, Ghulam R (BioMed Central, 2013)
BACKGROUND: Artesunate plus sulphadoxine-pyrimethamine (AS+SP) is now first-line treatment for Plasmodium falciparum infection in several south Asian countries, including Afghanistan. Molecular studies provide a sensitive means to investigate the current state of drug susceptibility to the SP component, and can also provide information on the likely efficacy of other potential forms of artemisinin-combination therapy. METHODS: During the years 2007 to 2010, 120 blood spots from patients with P. falciparum malaria were obtained in four provinces of Afghanistan. PCR-based methods were used to detect drug-resistance mutations in dhfr, dhps, pfcrt and pfmdr1, as well as to determine copy number of pfmdr1. RESULTS: The majority (95.5%) of infections had a double mutation in the dhfr gene (C59R, S108N); no mutations at dhfr positions 16, 51 or 164 were seen. Most isolates were wild type across the dhps gene, but five isolates from the provinces of Kunar and Nangarhar in eastern Afghanistan had the triple mutation A437G / K540E / A581G; all five cases were successfully treated with three receiving AS+SP and two receiving dihydroartemisinin-piperaquine. All isolates showed the pfcrt SVNMT chloroquine resistance haplotype. Five of 79 isolates had the pfmdr1 N86Y mutation, while 52 had pfmdr1 Y184F; positions 1034, 1042 and 1246 were wild type in all isolates. The pfmdr1 gene was not amplified in any sample. CONCLUSIONS: This study indicates that shortly after the adoption of AS+SP as first-line treatment in Afghanistan, most parasites had a double mutation haplotype in dhfr, and a small number of isolates from eastern Afghanistan harboured a triple mutation haplotype in dhps. The impact of these mutations on the efficacy of AS+SP remains to be assessed in significant numbers of patients, but these results are clearly concerning since they suggest a higher degree of SP resistance than previously detected. Further focused molecular and clinical studies in this region are urgently required.